Neurological outcome in long-chain hydroxy fatty acid oxidation disorders - Mütze, Ulrike; Ottenberger, Alina; Gleich, Florian; Maier, Esther M.; Lindner, Martin; Husain, Ralf; Palm, Katja; Beblo, Skadi; Freisinger, Peter; Santer, René; Thimm, Eva; Vom Dahl, Stephan; et al. (Annals of Clinical and Translational Neurology, 2024)
Objective This study aims to elucidate the long-term benefit of newborn screening (NBS) for individuals with long-chain 3-hydroxy-acyl-CoA dehydrogenase (LCHAD) and mitochondrial trifunctional protein (MTP) deficiency, inherited metabolic diseases included in NBS programs worldwide. Methods German national multicenter study of individuals with confirmed LCHAD/MTP deficiency identified by NBS between 1999 and 2020 or selective metabolic screening. Analyses focused on NBS results, confirmatory diagnostics, and long-term clinical outcomes. Results Sixty-seven individuals with LCHAD/MTP deficiency were included in the study, thereof 54 identified by NBS. All screened individuals with LCHAD deficiency survived, but four with MTP deficiency (14.8%) died during the study period. Despite NBS and early treatment neonatal decompensations (28%), symptomatic disease course (94%), later metabolic decompensations (80%), cardiomyopathy (28%), myopathy (82%), hepatopathy (32%), retinopathy (17%), and/or neuropathy (22%) occurred. Hospitalization rates were high (up to a mean of 2.4 times/year). Disease courses in screened individuals with LCHAD and MTP deficiency were similar except for neuropathy, occurring earlier in individuals with MTP deficiency (median 3.9 vs. 11.4 years; p = 0.0447). Achievement of dietary goals decreased with age, from 75% in the first year of life to 12% at age 10, and consensus group recommendations on dietary management were often not achieved. Interpretation While NBS and early treatment result in improved (neonatal) survival, they cannot reliably prevent long-term morbidity in screened individuals with LCHAD/MTP deficiency, highlighting the urgent need of better therapeutic strategies and the development of disease course-altering treatment.